Air-slot assisted TM-pass waveguide polarizer based on lithium niobate on insulator. (November 2022) - Liu, Jia-Min; Zhang, De-Long
Highlights: A TM-pass polarizer based on an air-slot embedded TFLNOI waveguide is proposed. Designed structure supports only a TM mode while TE mode being in cut-off state. A symmetric tetragonal dipyramid air-slot is designed to degrade insertion loss. Both slot geometry and silica thickness take effects on polarization performance. Optimal device shows good performance and ultra-compactness valid for on-chip use. Abstract: An air-slot assisted TM-pass waveguide polarizer based on thin-film lithium niobate on insulator (TFLNOI) is proposed. It consists of a segment of ridge-type TFLNOI single-mode strip waveguide and an embedded air-slot. The air-slot has a symmetric tetragonal dipyramid structure consisted of a cuboid in the central part and two identical tetragonal pyramids in two sides, which function as polarization generation and adiabatic approximation to degrade insertion loss, respectively. Waveguide properties and transmission characteristics of the device were simulated using finite difference method. The results show that the waveguide structure with a properly designed geometry supports only a TM mode, while does not the TE mode, which is cut-off in the cuboid air-slot region. Slot length, width and silica substrate thickness all take considerable effects on the insertion loss and extinction ratio. Qualitative and comprehensible explanations are given for the effects. An optimized polarizer has been suggested that exhibits excellent polarization performance, including a larger extinction ratio of 28.4 dB, a lower insertion loss of 0.29 dB, and a broader bandwidth of ∼110 nm (1490–1600 nm) with an extinction ratio >20 dB and an insertion loss <0.5 dB. In addition, the proposed device has a length of only 13 µm satisfying on-chip use.